The algebraic expression uses the terms to denote symbols
sum of means addition
difference of means subtraction
product of means multiplication
quotient of means division
Here we have the term 6x
which actually means 6 times x or
6 multiplied by x
hence by multiplication we use the word product of
so we have the product of 6 and a number as our right answer
Answer:
Step 1: Simplify both sides of the equation.
8−2(3−x)=4x+6
8+(−2)(3)+(−2)(−x)=4x+6(Distribute)
8+−6+2x=4x+6
(2x)+(8+−6)=4x+6(Combine Like Terms)
2x+2=4x+6
2x+2=4x+6
Step 2: Subtract 4x from both sides.
2x+2−4x=4x+6−4x
−2x+2=6
Step 3: Subtract 2 from both sides.
−2x+2−2=6−2
−2x=4
Step 4: Divide both sides by -2.
−2x
−2
=
4
−2
Step-by-step explanation:
Hi, I think you forgot to write a part of the problem, could you write the rest in the comments please. I would be happy to help you
Answer:
no one wants to answer this because im hungry
Step-by-step explanation:
Answer:
63
Step-by-step explanation:
A triangle always has a total of 180 degrees
Since we know two we can solve for x
76+41+x=180
x=63